2023
DOI: 10.3390/agronomy13030836
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Drought Tolerance of Newly Developed Tissue-Cultured Canola Genotypes under Varying Irrigation Regimes

Abstract: Drought is a major abiotic stress that greatly affects canola growth, production, and quality. Moreover, water scarcity is projected to be more severe and frequent as a result of climate change, in particular in arid environments. Thereupon, developing drought-tolerant and high-yielding canola genotypes has become more critical to sustaining its production and ensuring global food security with the continuing population growth. In the present study, ten canola genotypes comprising six developed tissue-cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…However, the highest proline accumulation in leaves was at 50% ETc in comparison to the full irrigation (100 ETc) and mild drought stress conditions (75% ETc). Abiotic stresses increase proline accumulation in all plant parts, especially the leaves (Morsi et al, 2023). It was reported that proline accumulation was observed when transplanted olive cultivars were exposed to different levels of drought (Shaheen et al, 2011).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…However, the highest proline accumulation in leaves was at 50% ETc in comparison to the full irrigation (100 ETc) and mild drought stress conditions (75% ETc). Abiotic stresses increase proline accumulation in all plant parts, especially the leaves (Morsi et al, 2023). It was reported that proline accumulation was observed when transplanted olive cultivars were exposed to different levels of drought (Shaheen et al, 2011).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Hence, their juvenile stocks are usually cultured in the nursery to shape high-quality stocks for transplant to quickly regenerate a destroyed population at the understory layer. As abiotic stress, drought threatens plant growth and development by impairing botanic functions in the secondary metabolism [ 8 , 9 , 10 ], photosynthetic physiology [ 9 , 10 ], nutrition [ 2 , 8 ], and antioxidation [ 8 ]. Plants can perceive these changes and adjust themselves in multiple ways, resulting in essential adaptations to drought [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For medicinal plants, the process of drought adaptation is associated with changes in not only medicinal parameters but also eco-physiological variables. These plants are cultured in this way for several reasons; not only is it expected to improve the quality of medicines [ 8 , 9 , 13 ], but it can also promote drought resistance [ 4 , 14 ]. Therefore, the relationship between these two types of changes has a practical meaning for predicting changes in medicinal parameters by monitoring other plant responses.…”
Section: Introductionmentioning
confidence: 99%
“…The current Special Issue, titled "Crop Tolerance under Biotic and Abiotic Stresses," compiles one review and eleven original research papers from several research groups worldwide, including China [3,4], Colombia [5], Egypt [6], Hungary [7], Korea [8], Nigeria [9], Saudi Arabia [10][11][12], Spain [13], and Taiwan [14]. Concerning the experimental conditions, seven of the research studies were designed under controlled growth conditions [4,[6][7][8]10,12,14], while the remaining four were field experiments [5,9,11,13]. Regarding the topics, three-quarters of the articles are concentrated on research related to abiotic stress, including multiple abiotic stresses [14], salinity [3,8,[10][11][12], drought [5,6] and herbicides [7].…”
mentioning
confidence: 99%
“…Concerning the experimental conditions, seven of the research studies were designed under controlled growth conditions [4,[6][7][8]10,12,14], while the remaining four were field experiments [5,9,11,13]. Regarding the topics, three-quarters of the articles are concentrated on research related to abiotic stress, including multiple abiotic stresses [14], salinity [3,8,[10][11][12], drought [5,6] and herbicides [7]. Additionally, three papers address the subject of biotic stress [4,9,13].…”
mentioning
confidence: 99%